Optimizing composite ecological networks through Synergistic risk Management, ecological Conservation, and recreational Integration: A case study of Beijing’s shallow mountain regions - Lei Cao; Kaiping Wang; Xinyao Zhao; Yunlu Zhang (Ecological Indicators)
The rapid pace of urbanization has intensified conflicts between ecological conservation and the exploitation of natural resources, necessitating a renewed focus on balancing environmental protection with resource utilization. The integration of ecological protection and recreational functions into a composite ecological network offers a viable solution to address environmental challenges, enhance ecosystem service capacity, promote leisure and recreational activities, and stimulate regional economic development. Shallow mountainous regions, where urban–rural disparities and the overlap of natural habitats with human activities are pronounced, present critical areas of study. This research focuses on the shallow mountainous areas of Beijing, employing a combination of multivariate models, including ecological risk assessment (ERA), ecosystem service function evaluation, and recreational resource evaluation. The study also incorporates multivariate analytical methods such as recreational function evaluation, cold and hotspot analysis, and circuit theory to identify comprehensive source areas that simultaneously support ecological protection and recreation. By constructing composite corridors that facilitate both wildlife migration and human recreation, this study establishes a multifunctional ecological network. Key findings include: (1) The study identified 49 ecological source sites and 43 recreational source sites, along with 105 ecological corridors and 80 recreational corridors; (2) This research selected 54 ecological pinch points, 137 intersections between ecological and recreational corridors, and 283 alternative composite source points combining ecological and recreational resources; (3) This paper selected 140 composite source points and the construction of 128 composite corridors, 161 potential corridors, 371.82 km2 of risk prevention area, and 468.74 km2 of ecological protection area; (4) Network analysis revealed that the composite ecological network demonstrated superior closure, complexity, and connectivity compared to traditional methods; (5) This study proposed an optimization strategy for ecological spatial networks, based on the “patch-corridor-substrate” theory of landscape ecology, emphasizing 3 levels: ecological restoration, ecological protection, and the development of recreational systems. The multifunctional composite ecological network constructed in this study effectively mitigates ecological risks, enhances ecosystem services functions, and promotes the balanced integration of ecological conservation and sustainable economic activities, such as ecotourism and cultural heritage utilization. It provides a theoretical foundation and technical support for the coordinated optimization of ecological conservation and economic development in shallow mountainous regions globally.